Flavonoids and chalconoid isolated from flowers of cosmos bipinnatus cav. (asteraceae) - Hoang , Minh Hao; Vo , Thi Nga (Journal of Technical Education Science, 2016)
Leaves of the genus Cosmos have been studied in chemical constituents and biological activities in Vietnam. However, chemical constituents of Cosmos flowers have not been extensively investigated. The dried purple and white flower powders of Cosmos bipinnatus Cav. were exhautively macerated with ethanol solvent. The extract was concentrated under reduced pressure to give the ethanolic extract. The extract was subjected to column chromatography (CC) with gradient elution (petroleum ether ® chloroform ® ethyl acetate) to give fractions. Thin layer chromatography (TLC) was used to analyze the fractions. The chloroform and ethyl acetate column factions were then further purified and analyzed by CC and TLC to obtain pure flavonoids and chalconoid (1-3) named 7, 3’, 4’-trihydroxy-6-methoxyaurone (1), 2’-hydroxy-4, 4’-dimethoxychalcone (2), and a mixture of 7, 2’, 5’-trihydroxyflavone (3a) and 5, 7, 3’, 4’-tetrahydroxyflavone (3b). Their chemical structure elucidation was accomplished by using 1D and 2D-NMR spectroscopy in combination with MS data.